313 STREAMLINING A ZOLEDRONIC ACID SERVICE TO A LEVEL TWO HOSPITAL. (25th October 2022) - Higgins, M; McGuirk, C; Devitt, L; Ludgate, S; Doyle, R; O'Donoghue, C; O'Dwyer, C; O'Hanlon, S
Abstract: Background: Approximately, 350-400 patients are admitted to a level 4 hospital for hip-fractures yearly (2019). According to the Irish Hip Fracture Database (2020) the average age for a hip-fracture is 81 years old. Patients post-hip fractures are commenced on Zoledronic acid; a bisphosphonate which is given intravenously 10 days post-surgery and then annually in year two and three. Zoledronic acid is a first line choice of bisphosphonate for the ≥65 population with a fragility fracture. Methods: 274 patients were transferred from the level 4 Hospital waiting list to a level 2 hospital waiting list to streamline the service. Meetings occurred to establish a pathway for the transition of services. A rapid improvement of the level 2 Day Hospital (DH) was commenced. Essential resources, training and information leaflets were developed in order to begin the service. A policy review, procedure guidelines and referral pathway were implemented. An excel database of patient information was transferred between organisations. The 274 patients were triaged by the DH. Pre-assessment phone calls were conducted determining if patients were still eligible for Zoledronic acid. Results: Of the 274 referrals; 24 had died; 30 refused; 37 were on other bone treatments and another 7 patients haven't made creatinine clearance, leaving 176. All 176 patients were allocated an appointment for 2022. Of the 176 patients; currently 57 patients have received their Zoledronic acid infusion in the DH. 69 of these referrals had an indicative date for their next Zoledronic acid infusion for dates after April 2022. There are 50 patients yet to receive their treatment which is overdue. Conclusion: With the prospect of service demands increasing due to Irelands aging population inevitably placing extra pressures on infusion suites in a level 4 hospital. The level 2 hospital has effectively managed to focus on tackling the backlog, streamlining referrals to the bone health service and thus reducing the risk of subsequent hip fractures.